Investigation of the effect of preload on the mechanical properties of fiber-reinforced geopolymer concrete - A. Sadr Momtazi; K. Gholipour; R. Kohani (مهندسی عمران شریف, 2022)
Concrete may be loaded at an early age for a variety of reasons. This loading can have negative and sometimes destructive effects on the hardened properties of concrete. Therefore, in the present study, the mechanical properties of fiber-reinforced geopolymer concrete after loading at an early age have been investigated. In the present study, the effect of preload on compressive strength at the ages of 28 and 90 days for geopolymer concrete containing fibers has been investigated. For this purpose, the samples were loaded at ages of 1, 3, and 7 days, equivalent to 30 and 70% of their compressive strength at the same age. The samples were then treated again in a humid environment and subjected to compressive loading at 28 and 90 days of age. The effect of preload on flexural strength as well as energy absorption of geopolymer concrete containing fibers was also investigated. Steel fibers with volumetric percentages of 0.25, 0.5, 0.75, and 1 and polypropylene fibers with volumetric percentages of 0.25, 0.5, and 0.75 were used in fabricating laboratory samples. The results demonstrate the positive effect of fibers on reducing the destructive effects of preload on compressive and flexural strength. The effect of fibers on reducing the destructive effects of 1-day preload is higher at higher loading percentage (70% pre-loading), such that the samples containing fibers with preload of 30% at the age of one day experienced a 28.8% increase in 28-day compressive strength, while this increase was 33.2% for the samples with preload of 70%. Samples containing 0.75% polypropylene fibers at 28 and 90 days of age compared to those containing 0.25 and 0.5% polypropylene showed less energy absorption on average due to preloading. In general, the design containing 0.25 polypropylene fiber and 1% steel fiber had the best result of flexural strength among preloaded samples.